Arabic–indonesian Code-mixing in Islamic Boarding Schools: Pedagogical Strategies, Identity Construction, and Symbolic Capital - Widiya Yul; Riko Andrian; Laela Asturi (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This study examines Arabic–Indonesian code-mixing practices in Islamic educational settings as a linguistic phenomenon shaping learning and social interaction. It aims to analyze the forms, functions, and contextual meanings of code-mixing across academic and non-academic domains. Employing a qualitative case study design, the study involved 32 students and one ustadz as key participants. Data were collected through participant observation, audio-recorded interactions, and semi-structured interviews, and analyzed thematically. The findings reveal that code-mixing is predominantly realized through the insertion of Arabic lexical elements. In academic contexts, it functions as a pedagogical and interactional strategy to mediate conceptual understanding, while in non-academic settings it serves as a marker of identity, solidarity, and symbolic capital. These findings highlight code-mixing as a valuable linguistic resource, contributing to the advancement of educational sociolinguistics and informing bilingual pedagogical practices in Islamic educational contexts.